Neurofilament Light Chain: A Candidate Biomarker of Perioperative Stroke - Zhang, Xiaoting; Wang, Huixian; Li, Li; Deng, Xiaoming; Bo, Lulong (Frontiers in Aging Neuroscience, 2022)
Perioperative stroke is defined as a brain infarction of ischemic or hemorrhagic etiology that occurs during surgery or within 30 days after surgery. However, identifying perioperative stroke is challenging. Thus, the discovery and validation of neurological biomarkers for perioperative stroke are urgently needed. Neurofilament forms part of the neuronal cytoskeleton and is exclusively expressed in neurons. After disease-related neuroaxonal damage occurs, neurofilament light chain protein is released into the cerebrospinal fluid and blood. Blood neurofilament light chain has recently been shown to serve as a potential marker of interest during the perioperative period. Therefore, the aim of the present review was to give an overview of the current understanding and knowledge of neurofilament light chain as a potential biomarker of perioperative stroke.